2014
DOI: 10.1111/codi.12616
|View full text |Cite
|
Sign up to set email alerts
|

Complete mesocolic resection and extended lymphadenectomy for colon cancer: a systematic review

Abstract: The available data for CME and EL have numerous fundamental limitations that prohibit adoption. Contemporary controlled studies are required before universal recommendation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(63 citation statements)
references
References 45 publications
2
57
0
4
Order By: Relevance
“…1 The weighted mean local recurrence rate in 5 years is approximately 4.5%. 2 It has been estimated that the number of deaths due to colorectal cancer will reach approximately 376 700 by 2020 in Asia. 3 Therefore, a better understanding of the molecular events involved in the prognosis of colon cancer is necessary and conducive to cancer detection and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…1 The weighted mean local recurrence rate in 5 years is approximately 4.5%. 2 It has been estimated that the number of deaths due to colorectal cancer will reach approximately 376 700 by 2020 in Asia. 3 Therefore, a better understanding of the molecular events involved in the prognosis of colon cancer is necessary and conducive to cancer detection and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…44,45 In their systematic review, Killeen et al reported 5-year local recurrence rate, overall survival rate, and disease-free survival rate of 4.5%, 58.1%, and 77.4%, respectively. 46 However, studies comparing laparoscopic excision to open CME raised issues regarding the completeness of laparoscopic excision for tumors near the flexures or in the transverse colon. 47,48 Authors attributed this to the technical difficulty of achieving a proximal ligation of the middle colic vessels laparoscopically, possibly explaining why transverse colectomies were excluded from most trials comparing laparoscopic versus open surgery for colorectal cancer.…”
mentioning
confidence: 99%
“…In a systematic review of 5,246 patients with right colon cancer, the 5-year DFS rate was 77.4% and the 5-year overall survival rate was 58.1% with a mean follow-up of 60 months. The local recurrence rate was 4.5% [25]. In the same review [25], the CME group saw more advantageous oncologic outcomes compared to the non-CME group.…”
Section: Discussionmentioning
confidence: 84%
“…The local recurrence rate was 4.5% [25]. In the same review [25], the CME group saw more advantageous oncologic outcomes compared to the non-CME group. It is possible that the improved outcomes of CME patients are related to the resection plane and the vessel site of ligation [26].…”
Section: Discussionmentioning
confidence: 84%